A Study On Causes Of Abnormal Noise That Affecting Ride Quality in MRT Putrajaya Line - Qasrin Najiha binti Mizan; Mohd Nazrul bin Roslan; Nor Effendi Yusof (Progress in Engineering Application and Technology, 2022)
MRT Putrajaya Line that act as a public transport, really pay full attention to ride quality as it is a very crucial thing and act as key of success for any public transport. However, the team happened to find out an abnormal noise issue when their train is running on the mainline during the dynamic testing and this may affect the ride quality as it bring discomfort to passengers. Therefore, this paper aim to analyze the possible causes of abnormal noise using cause and effect diagram and identify the root cause to propose a mitigation plan. By applying quality control tools, inspection sheet was used to collect the data to find the root cause of abnormal noise. While 5W1H method was used for the team to analyze the mitigation plan. Accordingly, the result shows that Obstacle Device Detector (ODD) produces a loud knocking sound due to excessive vibration from wheel out-of-roundness. The outcome from 5W1H analysis resulted to a decision for modification works on ODD spring and cam shaft and installation of additional holding bracket. Hence, this modification is expected to be applied for all train after it pass a testing and receiving an approval through Engineering Change Proposal (ECP).